2014
DOI: 10.4252/wjsc.v6.i2.173
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells in treating autism: Novel insights

Abstract: Autism spectrum disorders (ASDs) are complex neurodevelopmental disorders characterized by dysfunctions in social interactions, abnormal to absent verbal communication, restricted interests, and repetitive stereotypic verbal and non-verbal behaviors, influencing the ability to relate to and communicate. The core symptoms of ASDs concern the cognitive, emotional, and neurobehavioural domains. The prevalence of autism appears to be increasing at an alarming rate, yet there is a lack of effective and definitive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Indeed, two small open-label studies have shown symptom improvement in autistic people treated with MSCs [76,77]. However, problems still exist with this highly controversial cell-based therapy [78] and the mechanisms of action of MSCs has not been completely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, two small open-label studies have shown symptom improvement in autistic people treated with MSCs [76,77]. However, problems still exist with this highly controversial cell-based therapy [78] and the mechanisms of action of MSCs has not been completely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In light of recent clinical studies providing promising evidences for safety and efficacy of MSC transplantation in children suffering from autism, there is a necessity for preclinical models of MSC therapy for ASD to elucidate the restorative mechanisms involved in the beneficial outcome (Siniscalco et al, ). In this work, we demonstrated the potential of MSC treatment in an animal model for ASD and provided novel data relevant to the possible mechanisms in which MSC transplantation may act to trigger brain changes that could restore normal behavioral phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell based regenerative therapy was proposed for the treatment of ASD (Ichim et al, ) as studies have shown that cell transplantation may affect molecular mechanisms associated with ASD pathophysiology. In light of the above mentioned processes, mesenchymal stem cells (MSC) represent an attractive cell source for regenerative therapy for ASD (Siniscalco, Bradstreet, Sych, & Antonucci, ), as studies have shown MSC capacity to improve behavioral endophenotypes of animal models of brain diseases through inducing immunomodulation (Barhum et al, ; Chao, He, & Tay, ; Kassis et al, ; Rafei et al, ; Sheikh et al, ; Stemberger et al, ), enhancing neurogenesis (Bao et al, ; Kan, Barhum, Melamed, & Offen, ; Snyder, Chiu, Prockop, & Chan, ; Tfilin et al, ), increasing neurotrophic factor levels (Barzilay et al, ; Sadan et al, ; Sasaki et al, ; Wakabayashi et al, ; Wang et al, ; Zhang et al, ), and improving glutamatergic balance (Bae et al, ; Barzilay et al, ). We have recently shown that MSC transplantation to the cortex (Barzilay et al, ) and to the hippocampus (Barzilay et al, ) protects from deficits in social behavior following repeated treatment with the NMDA antagonist phencyclidine.…”
Section: Introductionmentioning
confidence: 99%
“…They found that children who completed this training have improved facial processing, at both the behavioral and electrophysiological level, suggesting therapeutic validity for this training system [39]. As we gain insight into the molecular basis of autism, though, there are many other avenues of therapy to pursue, including drug [40] and stem cell therapies [41]. These kinds of treatments are advantageous due to their ability to be tailored to each patient and because they target the biological basis of the disease rather than just the symptoms, however more extensive research is required before they can be clinically implemented.…”
Section: Therapiesmentioning
confidence: 95%